Innovation of Electronic-Based Multipurpose Credit Services to Improve Customer Satisfaction Through Loan Fee : A Study on Bank Jatim - Malang - Dwi Orbaningsih; Mellisa Gitaria; Wahyono Gendut Budi (Economics, Business, Accounting & Society Review, 2022)
The competition of financial services business is getting higher and encourages banks to optimize their efforts to reach as many prospective customers as possible. One of the efforts made is to update innovative banking credit services through the development of an electronic-based multipurpose credit service system. This research aims to find out whether the quality of service, product quality, and loan fee, affect customer satisfaction. This research uses a quantitative approach, data collection using questionnaires distributed to 150 customers of Jatim bank. Data analysis uses path analysis. This research found that The Quality of Service affects Customer Satisfaction but the Quality of Multipurpose Credit electronic application products does not significantly affect customer satisfaction; Quality of Service and Product Quality of Multipurpose Credit electronic application affects Customer Satisfaction through Loan Fees.  This research has the implication that innovation policies on multipurpose credit services and borrowing costs are major factors that can improve customer satisfaction.